Small-Molecule Ligands that bind the RET receptor activate neuroprotective signals independent of but modulated by coreceptor GFR α 1 - Jmaeff, Sean (2020)
Glial cell line-derived neurotrophic factor (GDNF) binds the GFRα1 receptor, and the GDNF-GFRα1 complex binds to and activates the transmembrane RET tyrosine kinase to signal through intracellular Akt/Erk pathways. To dissect the GDNF-GFRα1-RET signaling complex, agents that bind and activate RET directly and independently of GFRα1 expression are valuable tools. In a focused naphthalenesulfonic acid library from the National Cancer Institute database, we identified small molecules that are genuine ligands binding to the RET extracellular domain. These ligands activate RET tyrosine kinase and afford trophic signals irrespective of GFRα1 coexpression. However, RET activation by these ligands is constrained by GFRα1, likely via an allosteric mechanism that can be overcome by increasing RET ligand concentration. In a mouse model of retinitis pigmentosa, monotherapy with a small-molecule RET agonist activates survival signals and reduces neuronal death significantly better than GDNF, suggesting therapeutic potential. SIGNIFICANCE STATEMENT: A genuine ligand of RET receptor ectodomain was identified, which acts as an agonist. Binding and agonism are independent of a coreceptor glial cell line-derived neurotrophic factor family receptor α, which is required by the natural growth factor glial cell line-derived neurotrophic factor, and are selective for cells expressing RET. The lead agent protects neurons from death in vivo. This work validates RET receptor as a druggable therapeutic target and provides for potential leads to evaluate in neurodegenerative states. We also report problems that arise when screening chemical libraries.